Direct observation of the magnetic anisotropy of an Fe(II) spin crossover molecular thin film - Ashley S Dale; Saeed Yazdani; Thilini K Ekanayaka; Esha Mishra; Yuchen Hu; Peter A Dowben; John W Freeland; Jian Zhang; Ruihua Cheng (JPhys Materials, 2023)
In this work, we provide clear evidence of magnetic anisotropy in the local orbital moment of a molecular thin film based on the SCO complex [Fe(H _2 B(pz) _2 ) _2 (bipy)] (pz = pyrazol−1−yl, bipy = 2,2′−bipyridine). Field dependent x-ray magnetic circular dichroism measurements indicate that the magnetic easy axis for the orbital moment is along the surface normal direction. Along with the presence of a critical field, our observation points to the existence of an anisotropic energy barrier in the high-spin state. The estimated nonzero coupling constant of ∼2.47 × 10 ^−5 eV molecule ^−1 indicates that the observed magnetocrystalline anisotropy is mostly due to spin–orbit coupling. The spin- and orbital-component anisotropies are determined to be 30.9 and 5.04 meV molecule ^−1 , respectively. Furthermore, the estimated g factor in the range of 2.2–2.45 is consistent with the expected values. This work has paved the way for an understanding of the spin-state-switching mechanism in the presence of magnetic perturbations.